2023
DOI: 10.3390/plants12173040
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Responses to Human Trampling Indicate Alpine Plant Size Is More Sensitive than Reproduction to Disturbance

Nathalie Isabelle Chardon,
Philippa Stone,
Carly Hilbert
et al.

Abstract: Human disturbance, such as trampling, is an integral component of global change, yet we lack a comprehensive understanding of its effects on alpine ecosystems. Many alpine systems are seeing a rapid increase in recreation and in understudied regions, such as the Coast Mountains of British Columbia, yet disturbance impacts on alpine plants remain unclear. We surveyed disturbed (trail-side) and undisturbed (off-trail) transects along elevational gradients of popular hiking trails in the T’ak’t’ak’múy’in tl’a In’… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
2
0
0
Order By: Relevance
“…Similarly to what was demonstrated by [ 61 ], our study showed that the morphological traits of G. alypum are vulnerable to human trampling, while the reproductive ability appears not to be significantly affected. In fact, contrary to what was expected, our results provided no support for the hypothesis that human trampling causes differences in the reproductive capacity of G. alypum regardless of individual size.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly to what was demonstrated by [ 61 ], our study showed that the morphological traits of G. alypum are vulnerable to human trampling, while the reproductive ability appears not to be significantly affected. In fact, contrary to what was expected, our results provided no support for the hypothesis that human trampling causes differences in the reproductive capacity of G. alypum regardless of individual size.…”
Section: Discussionsupporting
confidence: 89%
“…The marked, statistically significant, differences in growth traits between the Central and peripheral (Intermediate and Extreme) zones of the path confirm, as demonstrated by [ 61 ], that these traits are sensitive to human trampling, which may lead to differential impacts on population persistence. In fact, we found that human trampling disturbance reduced the overall plant size, particularly the height and the maximum diameter, and, consequently, the plant biovolume, as a probable consequence of direct physical damage, including the breakage of stems, branches, and leaves.…”
Section: Discussionsupporting
confidence: 67%
“…In addition to the frequently covered effects of climate warming, many other human-made changes have important impacts on the survival of arctic and alpine plants. Chardon et al [ 13 ] explored the response of arctic shrubs and graminoids to human trampling, an integral component of global change; however, a comprehensive understanding of the effects of trampling on alpine and arctic ecosystems is lacking. The authors surveyed trail-side (disturbed) and off-trail (undisturbed) transects along altitudinal gradients in the Garibaldi Provincial Park in Canada.…”
mentioning
confidence: 99%